2002
DOI: 10.1002/em.10067
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the presence of mutagenic arylamines in human breast milk and DNA adducts in exfoliated breast ductal epithelial cells

Abstract: Aromatic and heterocyclic amines are ubiquitous environmental mutagens present in combustion emissions, fried meats, and tobacco smoke, and are suspect human mammary carcinogens. To determine the presence of arylamines in breast tissue and fluid, we examined exfoliated breast ductal epithelial cells for DNA adducts and matched human milk samples for mutagenicity. Breast milk was obtained from 50 women who were 4 -6 weeks postpartum, and exfoliated epithelial-cell DNA was evaluated for bulky, nonpolar DNA adduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…It was previously found [Thompson et al, 2002] that human breast milk exhibits mutagenic activity. The same study showed that most of the mutagenicity is in the basic fraction of the milk, which implies that basic compounds such as aromatic and heterocyclic amines, and polycyclic aromatic hydrocarbons contribute to the observed mutagenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously found [Thompson et al, 2002] that human breast milk exhibits mutagenic activity. The same study showed that most of the mutagenicity is in the basic fraction of the milk, which implies that basic compounds such as aromatic and heterocyclic amines, and polycyclic aromatic hydrocarbons contribute to the observed mutagenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Thompson et al [2002] showed that epithelial cells from human breast milk that had mutagenic activity contained bulky DNA adducts. The presence of DNA-carcinogen adducts was earlier demonstrated in human breast tissue [Perera et al, 1995;Li et al, 1996] and in cultured human epithelial cells [Swaminathan et al, 1994].…”
Section: Discussionmentioning
confidence: 99%
“…[92][93][94][95] However, the genotoxicity of aromatic amines is not exclusive to the target organ of tumorigenesis. 24,[94][95][96][97][98] This suggests that an alternative mode of action (epigenetics) may also exist that singly or in combination with genotoxicity can explain the bladder-specific tumorigenicity of aromatic amines. 24 The concept of a chemical carcinogen exerting its biological effects through epigenetic changes is very novel, and has never been investigated comprehensively.…”
Section: Smoking-related Bladder Cancer and Tobacco Smoke-derived Aromentioning
confidence: 99%
“…In five determinations the 2-Amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP) (Ͼ97% pure) was cell number ranged from 3.2ϫ10 4 /ml breast milk to 1.08ϫ10 6 /ml, in line with obtained from Toronto Research Chemicals (Toronto, Canada). All other published values (14). The numbers of epithelial cells present were measured chemicals, including o-toluidine, were obtained from Sigma Chemical Co.…”
Section: Methodsmentioning
confidence: 99%
“…Donors whose untreated cells contained the most DNA damage tended to from freshly expressed milk provides a ready source, obtained yield genotoxic breast milk extracts. Cells isolated from non-invasively, of HMECs in which to study the presence of, milk activated the rodent mammary carcinogens o-toluidine and their susceptibility to, DNA damage (14,15). Analysis, in and 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine tandem, of the milk from which the cells were obtained (PhIP).…”
Section: (81-97% Viability After Treatment) Comparisons Betweenmentioning
confidence: 99%